Education On The Use Of Pumpkin Pudding As A Measure To Control Hypertension In The Community Of RT 10, Jembatan Kecil Village - Fuji Fuji; Preti Preti; Tiara A; Tiara E; Mewi Mewi; Iin Iin (Jurnal Inovasi Kerja Nyata, 2026)
Hypertension is a public health problem with increasing prevalence and contributing to a high risk of cardiovascular disease. One of the main factors influencing this condition is an unbalanced diet, particularly high salt consumption and low nutritional intake. This community service activity aims to improve community knowledge and skills in managing hypertension through the implementation of a healthy diet based on local foods, specifically the use of pumpkin as a healthy snack alternative. The activity was conducted in Neighborhood Association (RT) 10, Jembatan Kecil Village, and involved 24 women as participants. The methods used included counseling, a demonstration of making pumpkin pudding, and an interactive discussion. The results of the activity showed an increase in participants' understanding of the relationship between diet and blood pressure control, as well as an increased awareness of the importance of choosing low-salt, nutritious snacks. Participants also demonstrated high enthusiasm and readiness to implement healthy eating patterns in their daily lives. Thus, practice-based education and the use of local foods have proven to be an effective and applicable approach in supporting hypertension prevention and control efforts at the community level.